Design and analysis rear diffuser for HEV model - Mohd Syazrin, Sopnan (2008)
The performance and handling of automobile are significantly affected by its aerodynamic properties. One of the main causes of aerodynamic is about drag force and lifting force. This will influence all the aspect of the vehicles such as overall performance, fuel consumption, safety and stability. The ground effect uses the airflow between the rod surface and the vehicle underbody to create a downforce. Rear diffuser will produce low pressure in causing overall lift to be lowered down to negative values. The negative value is occurring depends on the diffuser cross- section area. Rear diffuser will reduce the flow separation at the rear that causing the turbulent airflow. The wake region also will be reduced and this will make the drag force that produce at the rear vehicle reduced. By the lower drag force will contribute to the lower fuel consumption. The task was done by doing a Computational Fluid Dynamic (CFD) analysis for expected vehicle speed of 40-140 km/h. A drag force was found based on Finite Element Method (FEM) based on inputs from CFD. This force was calculated to produce the drag coefficient of the model as a whole. The approach needed to justify the amount of drag that can be reduced by addition of a rear diffuser as compared to the model without a diffuser. In an aerodynamic field, the main important thing to get the stability, performance and good fuel consumption is to design a vehicle with low CD. The reduction of lift and flow separation is the key results that will be a point of discussion. This project is to get an overall comparison of the velocity and pressure distribution before and after the rear diffuser is added.